2007
DOI: 10.1139/g07-031
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide linkage disequilibrium analysis in bread wheat and durum wheat

Abstract: Bread wheat and durum wheat were examined for linkage disequilibrium (LD) using microsatellite markers distributed across the genome. The allele database consisted of 189 bread wheat accessions genotyped at 370 loci and 93 durum wheat accessions genotyped at 245 loci. A significance level of p< 0.001 was set for all comparisons. The bread and durum wheat collections showed that 47.9% and 14.0% of all locus pairs were in LD, respectively. LD was more prevalent between loci on the same chromosome compared with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
61
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 17 publications
13
61
1
1
Order By: Relevance
“…; Raboin et al, 2008), sunflower (H. annuus;Fusari et al, 2008), tomato (Mazzucato et al, 2008;van Berloo et al, 2008) and wheat (Triticum spp. ; Somers et al, 2007). In S. peruvianum and S. chilense intragenic LD decayed within 150 and 750 bp, respectively, suggestive of high recombination rates and large effective population sizes in these species (Arunyawat et al, 2007).…”
Section: Neutrality Testsmentioning
confidence: 98%
“…; Raboin et al, 2008), sunflower (H. annuus;Fusari et al, 2008), tomato (Mazzucato et al, 2008;van Berloo et al, 2008) and wheat (Triticum spp. ; Somers et al, 2007). In S. peruvianum and S. chilense intragenic LD decayed within 150 and 750 bp, respectively, suggestive of high recombination rates and large effective population sizes in these species (Arunyawat et al, 2007).…”
Section: Neutrality Testsmentioning
confidence: 98%
“…Whole genome LD studies in the selfer A. thaliana have shown a longer extent of LD, up to 250 kb (Nordborg et al 2002). LD in bread wheat collections extended 1-5 cM (Chao et al 2007;Horvath et al 2009;Somers et al 2007). Longer LD extent may be due to longer stretches between the sampled loci that overlooks local gene conversion events and only displays crossing over events (Plagnol et al 2006).…”
Section: Lr10 Diversity Within and Between Populationsmentioning
confidence: 99%
“…In durum wheat (Triticum durum), LD stretches for a long distance (Maccaferri et al 2005), with high LD values found between loci located 50 cM apart. In bread wheat collections (T. aestivum), LD extent ranged from 1 cM to 5 cM (Chao et al 2007;Horvath et al 2009;Somers et al 2007). In Aegilops tauschii, the wild donor of the D genome to T. aesitvum, a 1400 bp LD block was observed in the grain softness locus (Massa and…”
Section: Introductionmentioning
confidence: 99%
“…However, intrachromosomal LD was much higher with r 2 = 0.551 (chromosome 2D) or r 2 = 0.909 (chromosome 5A) and decayed within a distance of < 1 cM (2D) and < 5 cM (5A) (Breseghello and Sorrells, 2006). In the study of the bread and durum wheat cultivars Somers et al (2007) observed that only a small fraction of the locus pairs approximately 2-3 cM apart showed r 2 values > 0.2, but few loci at longer distances showed high levels of LD with r 2 = 0.7 and 1.0 at 25.5 and 41.2 cM, respectively. In subpopulations LD extended for longer distances and even higher r 2 values were detected (Somers et al, 2007).…”
Section: Linkage Disequilibrium Measurement Visualization and Scope mentioning
confidence: 86%
“…In the study of the bread and durum wheat cultivars Somers et al (2007) observed that only a small fraction of the locus pairs approximately 2-3 cM apart showed r 2 values > 0.2, but few loci at longer distances showed high levels of LD with r 2 = 0.7 and 1.0 at 25.5 and 41.2 cM, respectively. In subpopulations LD extended for longer distances and even higher r 2 values were detected (Somers et al, 2007). Studies of LD across specific genomic regions were carried out for the region surrounding the yellow rust resistance gene Yr17 (Rhone et al, 2007) and for the region of QSng.sfr-3BS, a major QTL for resistance to Stagonospora nodorum glume blotch on chromosome 3B (Tommasini et al, 2007).…”
Section: Linkage Disequilibrium Measurement Visualization and Scope mentioning
confidence: 99%